Anatomical basis for sciatic nerve block at the knee level - Barbosa,Fabiano Timbó (2015)
BACKGROUND AND OBJECTIVES: Recently, administration of sciatic nerve block has been revised due to the potential benefit for postoperative analgesia and patient satisfaction after the advent of ultrasound. The aim of this study was to describe the anatomical relations of the sciatic nerve in the popliteal fossa to determine the optimal distance the needle must be positioned in order to realize the sciatic nerve block anterior to its bifurcation into the tibial and common fibular nerve. METHOD: The study was conducted by dissection of human cadavers' popliteal fossa, fixed in 10% formalin, from the Laboratory of Human Anatomy and Morphology Departments of the Universidade Federal de Alagoas and Universidade de Ciências da Saúde de Alagoas. Access to the sciatic nerve was obtained. RESULTS: 44 popliteal fossa were analyzed. The bifurcation of the sciatic nerve in relation to the apex of the fossa was observed. There was bifurcation in: 67.96% below the apex, 15.90% above the apex, 11.36% near the apex, and 4.78% in the gluteal region. CONCLUSIONS: The sciatic nerve bifurcation to its branches occurs at various levels, and the chance to succeed when the needle is placed between 5 and 7 cm above the popliteal is 95.22%.